Determination of microplastics in water body at Kelantan Bay and Pattani Bay - Nurain Saipolbahri (2020)
Microplastics debris (<5 mm) is a prolific environmental pollutant, found worldwide in marine, freshwater and terrestrial ecosystem. Interactions between biota and microplastics are prevalent and there is growing evidence that microplastics can incite significant health effects in exposed organisms. However, little attention was paid on the water bodies environment, though the fact that plastic debris can escape as wind-blown debris was previously reported. Thus, characteristics of microplastics in the water bodies fallout at Malaysia and Thailand bay were preliminarily studied. In this study, successive photography microscope and micro-Fourier Transform Infrared Spectroscopy equipped with Attenuated Total Reflection (µ-ATR-FTIR) were implemented to establish a highly accurate microplastics detection system. The method was applied to determine the presence of microplastics and characterize them according to their characteristics of plastics. In Kelantan bay, Malaysia, polypropylene microplastics being the most abundance ones, meanwhile, polyethylene microplastics were found to be the most abundance in Pattani bay, Thailand. The differences of microplastics found in both water bodies might be due to activities done near the bay.